2013
DOI: 10.1007/s10396-013-0457-0
|View full text |Cite
|
Sign up to set email alerts
|

JSUM ultrasound elastography practice guidelines: breast

Abstract: Ten years have passed since the first elastography application: Real-time Tissue Elastography™. Now there are several elastography applications in existence. The Quality Control Research Team of The Japan Association of Breast and Thyroid Sonology (JABTS) and the Breast Elasticity Imaging Terminology and Diagnostic Criteria Subcommittee, Terminology and Diagnostic Criteria Committee of the Japan Society of Ultrasonics in Medicine (JSUM) have advocated breast elastography classifications for exact knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 41 publications
2
49
1
3
Order By: Relevance
“…Guidelines have been proposed by EFSUMB (Cosgrove, Piscaglia et al 2013) and JSUM (Nakashima et al 2013). The WFUMB Guidelines and Clinical Practice Recommendations for Elastography of Breast advocate an elastography classification table (Table 1) to help organize and understand the wide variety of elastographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines have been proposed by EFSUMB (Cosgrove, Piscaglia et al 2013) and JSUM (Nakashima et al 2013). The WFUMB Guidelines and Clinical Practice Recommendations for Elastography of Breast advocate an elastography classification table (Table 1) to help organize and understand the wide variety of elastographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…The principal of sonoelastography can be divided into two types: strain and shear wave elastography [44]. Strain elastography is based on the distortion due to vibration caused by manual pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The first ultrasound elastography device, called Real-time Tissue Elastography TM (RTE), was released by Hitachi Medical (Hitachi Medical Corporation, Ldt., Tokyo, Japan) Corporation in 2003, after a joint development with Shiina et al 18,19 In the early stages after its development, ultrasound elastog-raphy was used in the diagnosis of mammary tumors, but, recently, its use was expanded to include the diagnosis of several organs. [20][21][22][23][24][25] Elastography is also used to examine the pancreas. In 2005, Hirooka et al first reported elastography of the pancreas by EUS, and Uchida et al first reported elastography by transabdominal US.…”
Section: Basic Principle Of Elastographymentioning
confidence: 99%